Multicentre evaluation of the Check-Direct CPE® assay for direct screening of carbapenemase-producing Enterobacteriaceae from rectal swabs. (29th January 2015) - Huang, Te-Din; Bogaerts, Pierre; Ghilani, Enes; Heinrichs, Amélie; Gavage, Pierre; Roisin, Sandrine; Willems, Elise; Verbruggen, Anne-Marie; Francart, Hugo; Denis, Olivier; Senterre, Jean-Marc; Glupczynski, Youri
Abstract: Objectives: The objective of this study was to evaluate in a multicentre survey the analytical performance of the Check-Direct CPE® assay (CDCPE), a multiplex PCR assay for the detection of carbapenemase-producing Enterobacteriaceae (CPE), directly from rectal swabs. Methods: Adult patients admitted to a high-risk unit in four participating centres were prospectively screened for CPE carriage by rectal swabbing. Samples were cultured on chromogenic CPE-selective media in the local laboratories. All growing Enterobacteriaceae strains were transferred for confirmation of carbapenemase production by multiplex PCR, together with the faecal swabs for CDCPE, to the coordinating laboratory. Results: Overall, 38 of the 394 samples analysed (9.6%; range 3%–20% per centre) yielded a positive signal for a carbapenemase gene with CDCPE, including 17 samples (4.3%; range 0%–15% per centre) that grew a total of 25 CPE-confirmed isolates (all OXA-48-like producers, including one isolate that simultaneously harboured a VIM-type carbapenemase). No CPE culture-positive samples were missed by CDCPE. Among the 21 samples that were CPE-positive with CDCPE but negative on culture, five were collected from previously known CPE carriers and 6/9 OXA-48-positive signals were detected at one participating centre that was undergoing a hospital-wide outbreak of OXA-48 CPE. When compared with the selective culture, the sensitivity and specificity of CDCPE were 100% and 94%, respectively. Conclusions: This study showed the value of CDCPE as a tool for screening CPE carriage in an epidemiological setting with a high prevalence of OXA-48 CPE. However, the potential added value for infection control management remains to be demonstrated.